Incidence and Outcome of Aneurysmal Subarachnoid Hemorrhage: The Swiss Study on Subarachnoid Hemorrhage (Swiss SOS). Issue 1 (January 2021) - Schatlo, Bawarjan; Fung, Christian; Stienen, Martin N.; Fathi, Ali R.; Fandino, Javier; Smoll, Nicolas R.; Zumofen, Daniel; Daniel, Roy Thomas; Burkhardt, Jan-Karl; Bervini, David; Marbacher, Serge; Reinert, Michael; et al.
Abstract : Background and Purpose: The purpose of this study was to assess nationwide incidence and outcomes of aneurysmal subarachnoid hemorrhage (aSAH). The Swiss SOS (Swiss Study on Subarachnoid Hemorrhage) was established in 2008 and offers the unique opportunity to provide this data from the point of care on a nationwide level. Methods: All patients with confirmed aneurysmal subarachnoid hemorrhage admitted between January 1, 2009 and December 31, 2014, within Switzerland were recorded in a prospective registry. Incidence rates were calculated based on time-matched population data. Admission parameters and outcomes at discharge and at 1 year were recorded. Results: We recorded data of 1787 consecutive patients. The incidence of aneurysmal subarachnoid hemorrhage in Switzerland was 3.7 per 100 000 persons/y. The number of female patients was 1170 (65.5%). With a follow-up rate of 91.3% at 1 year, 1042 patients (58.8%) led an independent life according to the modified Rankin Scale (0–2). About 1 in 10 patients survived in a dependent state (modified Rankin Scale, 3–5; n=185; 10.4%). Case fatality was 20.1% (n=356) at discharge and 22.1% (n=391) after 1 year. Conclusions: The current incidence of aneurysmal subarachnoid hemorrhage in Switzerland is lower than expected and an indication of a global trend toward decreasing admissions for ruptured intracranial aneurysms. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03245866. Abstract : Supplemental Digital Content is available in the text.